Odessa sea [large type] - Cussler, Clive; Cussler, Dirk (Cussler, Clive. Dirk Pitt adventure., 2016)
A desperate attempt in 1917 to preserve the wealth and power of the Romanov Empire. A Cold War bomber lost with a deadly cargo. Mysterious deaths on the Black Sea linked to modern day smugglers of nuclear materials. At the center of it all is Dirk Pitt and his team from NUMA. As the danger escalates, there's only one man who can avert catastrophe. From London to Washington, from the Black Sea to the Mediterranean, the action never stops, as Pitt races to prevent the next global war.